2015
DOI: 10.1002/14651858.cd008736.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vector and reservoir control for preventing leishmaniasis

Abstract: Background Leishmaniasis is caused by the Leishmania parasite, and transmitted by infected phlebotomine sandflies. Of the two distinct clinical syndromes, cutaneous leishmaniasis (CL) affects the skin and mucous membranes, and visceral leishmaniasis (VL) affects internal organs. Approaches to prevent transmission include vector control by reducing human contact with infected sandflies, and reservoir control, by reducing the number of infected animals. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 52 publications
1
46
0
3
Order By: Relevance
“…In Brazil, visceral leishmaniasis (VL) is caused by Leishmania (Leishmania) chagasi and shows a wide territorial distribution among areas of different geographic, climatic and social aspects [ 2 ]. Dogs are considered important reservoirs in endemic areas [ 3 ]. The prevalence of canine visceral leishmaniasis (CVL) in the Brazilian Northeast region, ranging from in 16 % in Garanhuns to 40.3 % in Paulista, Pernambuco state [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, visceral leishmaniasis (VL) is caused by Leishmania (Leishmania) chagasi and shows a wide territorial distribution among areas of different geographic, climatic and social aspects [ 2 ]. Dogs are considered important reservoirs in endemic areas [ 3 ]. The prevalence of canine visceral leishmaniasis (CVL) in the Brazilian Northeast region, ranging from in 16 % in Garanhuns to 40.3 % in Paulista, Pernambuco state [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same treatment can be applied to screens, curtains, sheets, and clothing (clothing should be retreated after five washings). González et al (2015) concluded that using insecticides to reduce sandfly numbers was effective at reducing CL incidence in some settings. However, there was insufficient evidence to know whether it was better to spray the internal walls of houses or to use insecticide impregnated bed-nets, curtains, bed-sheets or clothing.…”
Section: Review and Discussionmentioning
confidence: 99%
“…In the case of Tr yp an os om a, Leishmania,a ndPlasmodium, an alternative approach is the interruption of disease transmission by either preventing contacts between human beings and vectors, killing or altering the vector life cycle. However, the effectiveness of vector control is limited by the development of insecticide resistance [7][8][9]. Therefore, it is necessary to improve the current chemotherapy arsenal against these protozoan parasites and their vectors.…”
Section: Introductionmentioning
confidence: 99%